Strengthening bank regulation and supervision : National progress and gaps - Dordevic, Ljubica (Washington, D.C Fonds Monetaire International, 2021)
The paper employs two complementary strategies. First, it is pursues textual analysis (text mining) of the assessment reports to identify successes and challenges the authorities are facing. Second, it analyzes the grades in the Basel Core Principles assessments, including their evolution and association with bank fragility. (IMF page)
Glossary -- Executive Summary -- 1. Introduction -- 2. Adapting National Approaches to the International Reform Agenda -- 3. Taking Stock and the Lessons from Experience -- 4. Conclusions -- Annex 1. Econometric Analysis -- References
​Includes bibliographical references (P. 43-45).
Keywords: Banks and Banking; BANKS; BANKING; Bank management; state supervision; BANKING LAW